Predicting morbidity and mortality in Australian paediatric trauma with the Paediatric Age-Adjusted Shock Index and Glasgow Coma Scale. Issue 4 (April 2022) - Raythatha, Jineel H; Aulakh, Harleen; Yang, Stephen; Mok, Calvin; Soundappan, SV
Highlights: We evaluate the Pediatric age-adjusted shock index (SIPA) for the first time in Australia The First SIPA study to include pediatric trauma patients of all severity and ages shows that it loses correlation in the generalised population SIPA in combination with GCS (SIPAms) on arrival predicts morbidity outcomes more strongly than pre-arrival, but both predict more outcomes than SIPA without GCS. SIPAms increases sensitivity significantly for predictors of morbidity with a mild loss of specificity. aSIPAms has a sensitivity of 76% and specificity of 70% for major trauma. Abstract: Background: Paediatric age-adjusted shock index (SIPA) has emerged as a predictor of morbidity and mortality in trauma. Poor sensitivity and low generalisability demonstrated in previous studies have limited its use. We evaluate the use of SIPA in the general Australian paediatric trauma population and the combination of SIPA with GCS. Methods: All patients from January 2015 to August 2020 at a major Australian paediatric trauma centre were reviewed. Pre-arrival SIPA (pSIPA) and arrival SIPA (aSIPA) were calculated. If SIPA was elevated or the Glasgow Coma Scale ≤ 13, SIPA with mental state (SIPAms) was marked positive for pre-arrival (pSIPAms) and arrival (aSIPAms) respectively. Results/Discussion: Data from 480 patients were analysed. pSIPA and aSIPA poorly predicted outcomes of morbidity. Only aSIPA predicted mortality. However, both pre-arrival and arrival SIPAms variables predict mortality, major trauma (ISS≥12), hospital LOS, need for ICU admission, and major surgery. Furthermore, median ISS and lactate were significantly higher in positive pSIPA, aSIPA, pSIPAms, and aSIPAms groups than negative. aSIPAms has a sensitivity of 76% and specificity of 70% for major trauma. Conclusion: Broad inclusion criteria reduce SIPA's ability to predict morbidity. Combining it with GCS improves this and is most valuable when calculated at arrival. In addition, the score is more reliable for major trauma (ISS≥12). Future studies should evaluate the use of SIPAms in activation criteria.